(untitled) (ModaPalavra e-periódico, 2020)
This research aimed to understand the trajectory of the graduates of the first class of the fashion course of a public university. With this purpose we analyze the curriculum relations of the initial formation and the fields of action of the graduates from the formative course. Documents from the Course Feasibility Project (1996) and the graduates questionnaires (2001) were analyzed from the thematic analysis of Bardin (2016). The results demonstrate the technical characteristics of the curriculum due to th e practical context of the regional industrial clothing industry. Regarding the graduation course of the graduates demonstrated update to the Fashion market acting in intellectual fields between the service industry, industry and MEI.